Komponent kulturowy a proces przyswajania języka obcego - Mihułka, Krystyna (Neofilolog, 2012)
The aim of this article is to draw attention to the significance of a cultural component in the process of acquiring a foreign language. Presenting and discussing the definitions of cultural competence, the author of this article calls for the permanent inclusion of cultural competence in a foreign language lesson during which it could undergo constant development. Moreover, the author provides various interpretations of the term ‘knowledge of the foreign language’ laying particular emphasis on its colloquial and academic usage.